Growth curve of Nellore calves reared on natural pasture in the Pantanal - Santos, Sandra Aparecida; Souza, Geraldo Silva e; Costa, Ciniro [UNESP]; Abreu, Urbano Gomes Pinto de; Alves, Fabiana Villa; Ítavo, Luís Carlos Vinhas (Sociedade Brasileira de Zootecnia, 2011)
Weight-age and hip height-age relations of Nellore calves, from birth to 10 months old were fitted using a logistic model including sex and year of birth as fixed effects. Calves and their dams were reared on natural pasture using continuous grazing system. The crude protein content and total digestible nutrients were analyzed for pasture selected by the animals. The weights of the calves were adjusted to 205 days and 365 days. There were no significant effects of sex and birth year on the growth curve parameters, but there were significant effects of sex on hip height. The average weight (a parameter) at 10 months of age was 170 kg and the inflection point was observed at 93.5 days old. When weight-age and hip height-age curves were combined in the same graph, the intersection occurred at 142 days. The number of days to gain 160 kg from birth to 205 days of age (adjusted) and number of days to gain 240 kg from 205 days to slaughter was different between the birth years, which were probably due to the quality of the natural pastures. It is necessary to implement nutritional management strategies such as high quality pasture and/or feeding supplementation for calves once they reach three months of age.
Keywords: beef cattle; hip height; weanling weight